Additional notes on the publication of the Narrative, Zoology and Notes from a Journal of Research into the Natural History of the Voyage of H.M.S. Samarang and its consequences for the nomenclature of decapod crustaceans and other taxa - Low, Martyn E. Y.; Ng, Peter K. L.; Clark, Paul F. (Zootaxa, 2020)
Captain Edward Belcher was instructed by the Lords of the Admiralty to conduct a Surveying Expedition of the various coasts and islands in the Eastern Seas using H.M.S. Samarang. During this voyage from 1843–1846, Assistant-Surgeon Arthur Adams, made a significant contribution to the collection of natural history specimens, and together with fellow officers J. Richards and W. Browne, he prepared numerous drawings used by Belcher to illustrate the Narrative of the voyage. Later, Adams collaborated with Adam White (an Assistant in the Zoological Branch of the British Museum) to describe the Samarang Crustacea, published jointly with Lovell Reeve on the Samarang Mollusca, edited the Zoology of the voyage of H.M.S. Samarang and was the author of Notes from a Journal of the Natural History which was published in the Narrative of the voyage by Belcher. In his Natural History, Adams provided detailed accounts on some of the crustaceans collected with formal descriptions of species new to science thereby making these names available. The history, nomenclature and validity of the crustacean species cited in this work is discussed and a list of the available names is tabulated.